Point versus Band Targets for Inflation - Meredith Beechey; Pär Österholm (Örebro University School of Business, 2018)
Inflation targets come in different shapes and sizes. We explore the choice of a point or band target for inflation in a stylised economy in which agents learn about the inflation-generating process. We simulate under two conditions, namely i) a point inflation target and ii) a band inflation target from within which the central bank chooses its current spe-cific target. In many parameterizations of the model, the preferred target type rests on the inflation-output stabilization preferences of the central bank. A band target tends to be associated with higher volatility of inflation and lower volatility of the output gap than a point target. As such, a very strong preference for output stabilisation speaks in favour of a band inflation target.With preferences for inflation stabilisation closer to those thought to prevail in practice, a point target almost always outperforms a band target.
Keywords: E52; E58; 330; Inflation targeting; Learning; Constant gain least squares